PET Imaging and Neurohistochemistry Reveal that Curcumin Attenuates Brain Hypometabolism and Hippocampal Damage Induced by Status Epilepticus in Rats - Slowing, Karla; Gomez, Francisca; Delgado, Mercedes; Fernández de la Rosa, Rubén; Hernández-Martín, Nira; Pozo, Miguel Ángel; García-García, Luis (Planta Medica, 2022)
Numerous preclinical studies provide evidence that curcumin, a polyphenolic phytochemical extracted from Curcuma longa (turmeric) has neuroprotective, anti-inflammatory and antioxidant properties against various neurological disorders. Curcumin neuroprotective effects have been reported in different animal models of epilepsy, but its potential effect attenuating brain glucose hypometabolism, considered as an early marker of epileptogenesis that occurs during the silent period following status epilepticus (SE), still has not been addressed. To this end, we used the lithium-pilocarpine rat model to induce SE. Curcumin was administered orally (300 mg/kg/day, for 17 days). Brain glucose metabolism was evaluated in vivo by 2-deoxy-2-[18F]Fluoro-D-Glucose ([18F]FDG) positron emission tomography (PET). In addition, hippocampal integrity, neurodegeneration, microglia-mediated neuroinflammation, and reactive astrogliosis were evaluated as markers of brain damage. SE resulted in brain glucose hypometabolism accompanied by body weight (BW) loss, hippocampal neuronal damage, and neuroinflammation. Curcumin did not reduce the latency time to the SE onset, nor the mortality rate associated with SE. Nevertheless, it reduced the number of seizures, and in the surviving rats, curcumin protected BW and attenuated the short-term glucose brain hypometabolism as well as the signs of neuronal damage and neuroinflammation induced by the SE. Overall, our results support the potential adaptogen-like effects of curcumin attenuating key features of SE-induced brain damage.
Keywords: Curcumin; Curcuma longa; Zingiberaceae; lithium-pilocarpine model; [18F]FDG PET; neuroinflammation